CFD/FEA connected modeling and analysis of vapor cloud explosion at a wastewater storage pond of a chemical plant in Korea - Jang, Chang Bong; Han, Ji Yun; Jeong, Gun Sik; Baek, Ju Hong; Choi, Kwon Young; Jung, Seungho (Energy Science and Engineering, 2019)
This paper describes and reports an analysis of an explosion accident at a wastewater storage pond in South Korea, which resulted in six fatalities and one injury. This study was aimed at analyzing and determining the possibility of fracture of concrete structure by vapor cloud explosion (VCE) and ignition point of explosion, using computational fluid dynamics (CFD) for the explosion simulation. The result obtained via CFD analysis was connected with finite element analysis (FEA) to accurately review the structural damages resulting from the explosion. As a result, the mechanism of the accident was determined, and preventive solutions against such accidents are recommended.
Keywords: CFD analysis; Explosion accidents; Ignition points; Model and analysis; South Korea; Structural damages; Structural effect; Vapor cloud explosions; accident; case study; CFD; FEA; structural effect; VCE